1997
DOI: 10.1177/095632029700800504
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Biological Evaluation of 5′-O-Myristoyl Derivatives of Thymidine against Human Immunodeficiency Virus

Abstract: ; Fax: + 1 403 492 1217.--S ummary A series of 5'-O-acyl derivatives of thymidine (dThd) were prepared by direct acylation of thymidine using the Mitsunobu reaction. Further reaction of the bromo analogues with sodium azide gave azido ester analogues. Anti-human immunodeficiency virus type 1 (HIV-1) activities were determined against HIV-infeeted T4 lymphocytes. 5'-0-( 12-Azidododecanoyl)thymidine exhibited moderate activity (EC so 4.6 11M) against HIVinfected T4 lymphocytes. 5'-0-(2-Bromotetradecanoyl)-thymid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Complete analysis of the rest of the FTIR and 1H-NMR spectra was in supported the structure ascertained as 5 / -O-(acetyl)thymidine (2). This finding was in conformity with the mechanism proposed by Parang et al 25 Thymidine (1) on treatment with myristoyl chloride, afforded compound 7 and its FTIR spectrum the absorption bands at 1702 cm -1 for C=O stretching and 3398 cm -1 for -OH stretching. The 1 H-NMR spectrum displayed a two two-proton multiplet at δ 2.34 {CH 3 (CH 2 ) 11 CH 2 CO-}, and δ 1.74-1.48 {CH 3 (CH 2 ) 10 CH 2 CH 2 CO-}, a twenty-proton multiplet at δ 1.42-1.14 {CH 3 (CH2) 10 CH 2 CH 2 CO-}, and a three-proton triplet at δ 0.86 {CH 3 (CH 2 ) 12 CO-} suggested the attachment of one myristoyl group in the compound.…”
Section: Synthesis and Spectroscopic Characterizationsupporting
confidence: 88%
“…Complete analysis of the rest of the FTIR and 1H-NMR spectra was in supported the structure ascertained as 5 / -O-(acetyl)thymidine (2). This finding was in conformity with the mechanism proposed by Parang et al 25 Thymidine (1) on treatment with myristoyl chloride, afforded compound 7 and its FTIR spectrum the absorption bands at 1702 cm -1 for C=O stretching and 3398 cm -1 for -OH stretching. The 1 H-NMR spectrum displayed a two two-proton multiplet at δ 2.34 {CH 3 (CH 2 ) 11 CH 2 CO-}, and δ 1.74-1.48 {CH 3 (CH 2 ) 10 CH 2 CH 2 CO-}, a twenty-proton multiplet at δ 1.42-1.14 {CH 3 (CH2) 10 CH 2 CH 2 CO-}, and a three-proton triplet at δ 0.86 {CH 3 (CH 2 ) 12 CO-} suggested the attachment of one myristoyl group in the compound.…”
Section: Synthesis and Spectroscopic Characterizationsupporting
confidence: 88%
“…Use of a primary or a saturated achiral alcoholic substrate generally does not pose a problem in the Mitsunobu process, and hence, only a list of compounds wherein it is used is provided here. These include (i) photoresponsive esters with an azobenzene group, using the reaction of the mesogenic alcohols with fumaric acid or maleic acid, (ii) cyclohexyl nitronic ester by starting with cyclohexanol, (iii) polar functional PPV derivatives with ester groups for sensor applications, (iv) capsular polysaccharides, (v) acetylenic esters of 2,3-dibromomaleic acid and isophthalate esters as precursors for dendrimers, (vi) enfumafungin, (vii) buprestin A and B, (viii) cinnamyl monoglyceride, (ix) β-acyl glucuronides, (x) 17 O-enriched esters of carbohydrates with PhC(O) 17 OH, (xi) bromoacetylation of Wang resin, (xii) (±)-6-myoporol, (xiii) multiple porphyrin arrays through ester linkages, (xiv) 3,5-hexadienyl acrylates, (xv) mono- and di-esters of sucrose with long chain carboxylic acids, (xvi) ( S )-(−)-camphanic acid esters of (hydroxymethyl)pyrroles, (xvii) syn , syn -bicyclo[3.3.0]octyl-2-benzoate, (xviii) an esterification step in the synthesis of syn -enol ethers, (xix) glass forming liquid crystals, (xx) conjugated reactive mesogen 2-methyl-1,4-bis[2-(4-acryloylpropyloxyphenyl)ethenyl]benzene, (xxi) 6,6′-di- O - p -nitrobenzoyl-2,3,4,3′,4′-penta- O -benzyl-1′-methoxymethylsucrose, (xxii) poly(triacetylene) oligomers with ester linkages, (xxiii) β-anomers of bile acid 24-acyl glucuronides, , (xxiv) geodiamolide A (an 18-membered cytotoxic depsipeptide from marine sponges), (xxv) 5′- O -acyl derivatives of nucleosides, , (xxvi) the acetate of ( R )-1-indanol, (xxvii) side chain copolymers containing liquid crystalline and photoactive chromophores, (xxviii) dimethyl-3-((1 Z )-propenyl)cyclopropanecarboxylic acid methyl ester, (xxix) oligothiophene containing photorefractive material with NLO chromophore, and (xxx) 4-flurobenzyl 4-(4-nitrophenyl)butyrate . The structural drawings pertaining to these references are given in the Supporting Information (Table S2).…”
Section: Carboxylic Acids/phosphorus-based Acids As Nucleophiles: Est...mentioning
confidence: 99%
“…Different classes of chemicals have been screened all over the world. Nucleosides, especially acylated thymidine (Arifuzzan et al 2018) and uridine (Kawsar et al 2018, Sumi et al 2019) are very important due to their effective biological activity (Parang et al 1997, Johannes et al 2010. A literature survey revealed that a large number of biologically active compounds possess aromatic, heteroaromatic and acyl substituents (Hui et al 2002, Patel et al 2002.…”
Section: Introductionmentioning
confidence: 99%